2010
DOI: 10.4490/algae.2010.25.4.155
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidants from macroalgae: potential applications in human health and nutrition

Abstract: The underlying physiology of algal antioxidant compounds is reviewed in the context of seaweed biology and utilization. The application of seaweed antioxidants in foods, food supplements, nutraceuticals and medicine is considered from the perspective of benefits to human health. We advocate that direct consumption of seaweed products for their antioxidant composition alone provides a useful alternative to non-natural substances, while simultaneously providing worthwhile nutritional benefits. Economic utilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
108
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 243 publications
(122 citation statements)
references
References 127 publications
2
108
0
7
Order By: Relevance
“…The harvesting of Dulse is a significant cottage industry in Nova Scotia (MacFarlane 1964, 1966, Ffrench 1974. The edible alga can be eaten dried or wet, and can be used in cooking (e.g., Rhatigan 2009), and its antioxidant properties may have medicinal benefits (e.g., Yuan et al 2009, Cornish andGarbary 2010). There have been no significant studies of the Dulse harvest in this area since MacFarlane (1966) and Ffrench (1974), and few ecological studies of Dulse have been conducted in this part of the Bay of Fundy.…”
Section: Introductionmentioning
confidence: 99%
“…The harvesting of Dulse is a significant cottage industry in Nova Scotia (MacFarlane 1964, 1966, Ffrench 1974. The edible alga can be eaten dried or wet, and can be used in cooking (e.g., Rhatigan 2009), and its antioxidant properties may have medicinal benefits (e.g., Yuan et al 2009, Cornish andGarbary 2010). There have been no significant studies of the Dulse harvest in this area since MacFarlane (1966) and Ffrench (1974), and few ecological studies of Dulse have been conducted in this part of the Bay of Fundy.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that not only medical plants, but also algae contain beneficial non-nutritive agents such as polyphenols, chlorophylls, and sulfated polysaccharides, which possess antimutagenicity, anticarcinogenicity, and antioxidant activity (Cornish and Garbary, 2010;Lee et al, 2013). We previously demonstrated that the amounts of total phenolic compounds, total carbohydrates, and sulfates of the hot water extract were greater than those of raw materials (Thumvijit et al, 2013b).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, its use as flakes and in various cooked foods is becoming more widespread (e.g., Rhatigan 2009). Various aspects of chemical composition have been evaluated including lipid content (Mishra et al 1993) and antioxidants (e.g., Yuan et al 2009, Cornish andGarbary 2010). There are two traditional areas for the commercial harvesting of P. palmata in eastern Canada: Grand Manan Island in New Brunswick, and Digby Neck in Nova Scotia (e.g., Ffrench 1974).…”
Section: Methodsmentioning
confidence: 99%